(3GUhd GdGbJUGO GdSjGSjs - (3RjfH(B, (3MSjf YhV Gddgs ((3GdGScfOQjI(B:s (3OGQ GdLGeYjI ddfTQ(B,s, 2000)
(3GdHGH GdChd (B: (3aj JYQja Yde GdGbJUGO (B: (3GdaUd GdChd (B: (3aj JYQja Yde GdGbJUGO GdSjGSj (B: (3GdeHMK GdChd (B: (3GLJeGYjI Yde GdGbJUGO GdSjGSj (B: (3GdeHMK GdKGfj (B: (3GdaQhY GdCSGSjI dYde GdGbJUGO GdSjGSj (B: (3GdaUd GdKGfj (B: (3GdSjGSI GdGbJUGOjI hGdbQGQ GdGbJUGOj hOhQ QLd GdGbJUGO (B: (3GdeHMK GdChd (B: (3OhQ QLd GdGbJUGO (B: (3GdeHMK GdKGfj (B: (3GdYhGed GdeDKQI Ydi GJNGP GdbQGQ GdGbJUGOj (B: (3GdeHMK GdKGdK (B: (3GdeTcdI GdGbJUGOjI hGdeSCdI GdGbJUGOjI (B: (3GdaUd GdKGdK (B: (3GdGfJGL hYfGUQg (B: (3GdeHMK GdChd (B: (3GdYfUQ GdHTQj (B: (3GdeWdH GdChd (B: (3GdYed (B: (3GdeWdH GdKGfj (B: (3GdJfXje (B: (3GdeWdH GdKGdK (B: (3GdKhQI GdYdejI GdJcfhdhLjI (B: (3GdeHMK GdKGfj (B: (3YfGUQ GdEfJGL GdeGOjI (B: (3GdeWdH GdChd (B: (3QCS GdeGd (B: (3GdaUd GdQGHY (B: (3GdfGJL Gdbhej hGdONd Gdbhej (B: (3GdeHMK GdChd (B: (3GdfGJL Gdbhej (B: (3GdeHMK GdKGfj (B: (3GdGSJgdGc (B: (3GdeHMK GdKGdK (B: (3GdGONGQ (B: (3GdeWdH GdChd (B: (3Cge NUGFU GdfXGe GdGbJUGOj GdQCSeGdj (B: (3GdeWdH GdKGfj (B: (3Cge NUGFU GdfXGe GdGbJUGOj GdGTJQGcj (B: (3GdeWdH GdKGdK (B: (3GdfXe GdGbJUGOjI aj GbJUGOjGJ GdYGde GdeYGUQ (B: (3GdeHMK GdKGfj (B: (3GdhRf GdfSHj dbWGYGJ GdfTGW GdGbJUGOj heSJhi JWhQgG(B-(3GdHGH GdKGfj (B: (3fXQjI GdbjeI hGdCKeGf (B: (3GdaUd GdChd (B: (3GdfXQjGJ GdeaSQI ddbjeI (B: (3GdaUd GdKGfj (B: (3GdYQV(B-(3GdHGH GdKGdK (B: (3fXQjI GdEfJGL(B-(3GdHGH GdQGHY (B: (3fXQjI Sdhc GdeTQhY hGdCShGb(B-(3GdHGH GdNGeS (B: (3fXQI ehLRI aj fXQjI GdJhRjY(B. (3edNU(B: (3jJfGhd gPG GdcJGH aj JYQja Yde GdGbJUGO (B? (3aj JYQja Yde GdGbJUGO GdSjGSj(B- (3OhQ QLd GdGbJUGO (B? (3GdeTcdI GdGbJUGOjI hGdeSGdI GdGbJUGOjI (B? (3GdYfUQ GdHTQjs
Keywords: (3GbJUGO SjGSjs